Implementasi Mobile Ad-Hoc Network (Manet) Dengan Protokol AODV Pada Perangkat Berbasis NRF24L01 - Arief Indra Rivaldy Permana; Sabriansyah Rizqika Akbar; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Implementation of AODV protocol on Mobile Ad-Hoc Network (Manet) is basically done using simulation software. Using software like NS-3, OPNET or OMNET. Disadvantage of those simulation software is there is no obstacles because of the ideal condition. The lack of AODV protocol implementation on the manet is using real devices. To overcome the mistakes made by the software, in this study applied the implementation of mobile ad-hoc network (manet) by using AODV protocol on nRF24L01 hardware to send data inputted by user and to test the system functionality by running it with any obstacles like doors, walls, and glasses. From the results of this research, is that each node can communicate with each other on ad-hoc mobile network using Arduino UNO as microcontroller and nRF24L01 wireless module. The AODV protocol as an inter-node protocol routing method has been successfully implemented. Each node has also successfully process performed. On 15 times the system test functionality, where the scenario is a static node without any obstacles, the node moves dynamically without any obstacles and the node moves dynamically with the obstacles of doors, walls, or glasses, all nodes was sending and receiving data with the percentage of success is 86.6%. This proved that the system functionality has been successfully implemented properly.